A Comparative Study of Some Procedures for Isolation of Fruit DNA of Sufficient Quality for PCR-Based Assays - Fialová, Lenka; Langová, Denisa; Márová, Ivana (MDPI, 2020)
Food fraud has been and still is a problem in the food industry. It is detectable by several approaches, such as high performance liquid chromatography (HPLC), chemometric assays, or DNA-based techniques, each with its own drawbacks. This work addresses one major drawback of DNA-based methods, in particular their sensitivity to inhibitors contained in particular matrices from which DNA is isolated. We tested five commercial kits and one in-house method characterized by different ways of sample homogenization and DNA capture and purification. Using these methods, DNA was isolated from 10 different fruit species commonly used in plant-based foodstuffs. The quality of the DNA was evaluated by UV-VIS spectrophotometry. Two types of qPCR assays were used for DNA quality testing: (i) Method specific for plant ITS2 region, (ii) methods specific for individual fruit species. Based mainly on the results of real-time PCR assays, we were able to find two column-based kits and one magnetic carrier-based kit, which consistently provided fruit DNA isolates of sufficient quality for PCR-based assays useful for routine analysis and identification of individual fruit species in food products.

Food fraud has been and still is a problem in the food industry. It is detectable by several approaches, such as high performance liquid chromatography (HPLC), chemometric assays, or DNA-based techniques, each with its own drawbacks. This work addresses one major drawback of DNA-based methods, in particular their sensitivity to inhibitors contained in particular matrices from which DNA is isolated. We tested five commercial kits and one in-house method characterized by different ways of sample homogenization and DNA capture and purification. Using these methods, DNA was isolated from 10 different fruit species commonly used in plant-based foodstuffs. The quality of the DNA was evaluated by UV-VIS spectrophotometry. Two types of qPCR assays were used for DNA quality testing: (i) Method specific for plant ITS2 region, (ii) methods specific for individual fruit species. Based mainly on the results of real-time PCR assays, we were able to find two column-based kits and one magnetic carrier-based kit, which consistently provided fruit DNA isolates of sufficient quality for PCR-based assays useful for routine analysis and identification of individual fruit species in food products.
A Comparative Study of Some Procedures for Isolation of Fruit DNA of Sufficient Quality for PCR-Based Assays
Keywords: DNA isolation; real-time PCR; commercial kit; red fruit; Prunus; tropical fruit; DNA isolation; real-time PCR; commercial kit; red fruit; Prunus; tropical fruit